Pelatihan Aquascape: Pemeliharaan Dan Perawatan Aquascape Untuk Penguatan Usaha Perajin Aquascape - A Faroby Falatehan; YUSMAN; Sriwulan Ferindian Falatehan; Rizal Bahtiar (FEB-UP Press, 2024)
This aquascape training is a training held by Lecturers Serving Innovation at the Bogor Agricultural Institute. This training is the second training from the Lecturer Serving Innovation at the Bogor Agricultural Institute which contains information about aquascape maintenance and maintenance. The aim of this training is to strengthen the position of aquascape craftsmen in their business. The training was attended by 15 people and was held at the Food Security and Fisheries Service Office. Participants were asked to participate in practicing caring for and maintaining aquascape. One of the benefits of this training is the gathering of aquascape craftsmen, so that after this training it is hoped that they will be able to create an institution to strengthen the position of aquascape craftsmen, especially in the local government in Cirebon Regency.